The Effect of Deppamil Dangke in Increasung Upper Arm Circumference and Haemoglobin Levels in Pregnant Women with Chronic Energy Deficiency - Hermin Hermin; Mardiana Ahmad; Farid Husin; Andi Nilawati Usman; Martira Maddeppungeng; Suryani As'ad (Poltekkes Kemenkes Palu, 2023)
The prevalence of chronic energy deficiency in pregnant women in Indonesia is relatively high, requiring some actions to be taken to lower it. This study aims to analyze the roles of deppamil dangke administration in increasing upper arm circumference and haemoglobin levels in pregnant women with chronic energy deficiency (CED) in Enrekang Regency. This research is of the quasi-experimental type with a non-equivalent control group design. The population consisted of 28 CED pregnant women with gestational age >20 weeks using exhaustive sampling technique, there were two test groups involved, namely, an intervention group and a control group, each consisting of 14 samples. The intervention group was given deppamil dangke 6 pieces/day (60 gr) plus government food supplement while the control group was given government food supplement 3 pieces/day (100 gr) with an intervention duration of 18 weeks. UAC and haemoglobin levels were measured before and after the intervention. The results of this study indicated that there was an increase in the size of UAC in both groups but not significantly different as both the intervention and control groups experienced increases in upper arm circumference with the same p value (p = 0.001). But it was significant in increasing the hemoglobin level of CED pregnant women because the intervention group experienced a significant increase with a p- value of 0.020 while the control group had a p value of 0.506. Future.